2018
DOI: 10.1002/cctc.201800890
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline‐Water/Coordination Induced Formation of 3D Highly Porous Heteroatom‐Doped Ultrathin Carbon Nanosheet Networks for Oxygen Reduction Reaction

Abstract: Development of highly efficient electrocatalysts with low cost for oxygen reduction reaction (ORR) is crucial for their application in fuel cells and metal‐air batteries. In this work, we report a synthesis of 3D heteroatom‐doped ultrathin carbon nanosheet networks directly starting from solid raw materials. This method represents an operationally simple, general, and sustainable strategy to various ultrathin carbon nanosheet networks. Evaporation of crystalline water and coordination interaction are proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…2(f). The XPS results suggested that the high-resolution N 1s spectrum could be deconvoluted into four types: 398.4 ± 0.2, 400.0 ± 0.2, 401.0 ± 0.2, and 402.0 ± 0.2 eV, corresponding to pyridinic N, pyrrolic N, graphitic N, and oxidized N, respectively [18]. An essential feature of Cs-N/C was that the pyridinic N peak split.…”
Section: Resultsmentioning
confidence: 99%
“…2(f). The XPS results suggested that the high-resolution N 1s spectrum could be deconvoluted into four types: 398.4 ± 0.2, 400.0 ± 0.2, 401.0 ± 0.2, and 402.0 ± 0.2 eV, corresponding to pyridinic N, pyrrolic N, graphitic N, and oxidized N, respectively [18]. An essential feature of Cs-N/C was that the pyridinic N peak split.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 Therefore, a large number of ZIF-derived carbon nanomaterials such as carbon nanotubes and carbon nanosheets have been widely utilized in different energy-related applications, because of their large specific surface area, excellent electrical conductivity, high stability and other significant advantages. [24][25][26][27] In this context, the rational design and facile preparation of porous MOF-derived carbon-based catalysts in energy conversion and storage is highly important and desired.…”
Section: Introductionmentioning
confidence: 99%
“…Organics containing rich N atoms are ideal precursors for M–N–C. For example, polyacrylonitrile (PAN) is frequently used to synthesize M–N–C catalysts for ORR electrocatalysis. , As for metal-free carbon catalysts, nitrogen , and sulfur have been chosen as heteroatoms doped on carbon materials to facilitate the ORR performance.…”
Section: Introductionmentioning
confidence: 99%